Comparison of acute pressor effects of plain water, oral rehydration solution, and fruit juice ingestion in healthy young adults - Amatya, Mrigendra; Oli, K.; Pokhrel, S.; Shrestha, S. (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Ingestion of plain water is associated with an acute rise in blood pressure, probably due to elicitation of a sympathetic reflex in patients with autonomic dysfunction. Whether the pressor response is similar in healthy individuals is disputed. Other types of fluid could have different effects. Comparison of the pressor effects of plain water ingestion with other types of fluids has been reported scantily. Material and methods: In a cross-over experimental study, young medical students ingested 500 mL of plain water (PW), 500 mL of oral rehydration salt solution (ORS), or 400 mL of commercial fruit juice (FJ) on separate days, with at least two days’ gap. Their heart rate (HR) and blood pressure (BP: systolic, SBP and diastolic, DBP) were recorded before, immediately after (0 min), and at 2, 5, 20, and 40 min after fluid ingestion and compared with baseline values. Results: Sixty nine apparently healthy medical students (40 males and 29 females, age range 18-24 years) participated in the study. Compared to baseline, SBP and DBP were significantly higher at 0, 2, and 5 min measurements with ORS and FJ; then lowered at 20 and 40 min. With the PW, BP changes were not significant at any time of measurement. In all experimental set ups, HR increased significantly at 0, 2, and 5 min and lowered to near baseline levels then after. Conclusion: Ingestion of ORS and FJ, but not PW, is associated with acute pressor effects in healthy young adults. This finding could have implications on the choice of fluid for prophylaxis in hypotensive conditions such as blood donation, postural hypotension, and autonomic dysfunction.